BILINGUAL EDUCATION PROGRAM: TEACHERS' AND STUDENTS' PERSPECTIVES AND CHALLENGES AT SMAN SUMATERA SELATAN PALEMBANG - Ahmad Safei; Etty Pratiwi; Marleni Marleni (Esteem Journal of English Education Study Programme, 2023)
The objective of this study was to find out the teachers and students perceptions and the challenges that faced by the teachers and students in teaching and learning by using Bilingual Education Program at Senior High School of Sumatera Selatan Palembang. This study applied qualitative descriptive method. The population of this study was 4 science and math teachers and 25 of 10th grade students. The data were collected by using close- ended questionnaire and interview. The results showed that Bilingual education program is a good program. There were so many benefits for the teachers and students. This program required the teachers and students to speak English even the subject are mathematics and science. Bilingual was giving the chance for the teachers and students to get new experiences. The teachers and students reported to having limited English skills and particularly in terms of scientific terminology.